Consulting opportunities with the ADB. (Manila Asian Development Bank, 1995)
Each year, the Asian Development Bank employs some 600 consultants to carry out technical assistance activities and other operations. Any individual consultant or consulting frim from a member country of the ADB can pursue these opportunities. It pays, however, to be well informed. Where does one learn of upcoming loan and technical assistance activities? Why is an expression of interest important? What should a proposal include?
It provides an overview of the selection and recruitment of consultant firms and indiviudals. The information contained in this video is vital for consultants who wish to avail of consulting opportunities offered by the ADB.